A one meter class eye for the PLAnetary Transit and Oscillation spacecraft. (October 2015) - Ragazzoni, Roberto; Rauer, Heike; Catala, Claude; Magrin, Demetrio; Piazza, Daniele; Pagano, Isabella; Nascimbeni, Valerio; Piotto, Giampaolo; Bodin, Pierre; Levacher, Patrick; Farinato, Jacopo; Viotto, Valentina; et al.
Abstract: PLATO stands for PLAnetary Transits and Oscillations and it is the forthcoming third Medium sized mission of ESA, planned to be launched in 2024. Its optical payload is an ensemble of 34 small telescopes that mimic a single one meter class aperture with a huge Field of View of more than 50° in size. Aiming to find exoplanets around bright nearby stars it is designed to discover a significant number of relatively nearby Earth-like worlds. A description of the optomechanical adopted solution and a speculative scenario to further explore such alien worlds is briefly given.